LANGUAGE SHIFT AMONG MIDDLE-AGE AND OLDER CHINESE DESCENDANTS IN PENANG, MALAYSIA: A BITTER SWEET TALE - Ong, Teresa Wai See; Troyer, Robert A. (UC Journal: ELT, Linguistics and Literature Journal, 2024)
Chinese heritage languages play a vital role in the lives of the Chinese-Malaysian community because they act as important markers of their heritage identity. However, due to globalisation and modernisation processes taking place at present-day, the global language, Mandarin Chinese, has begun to take over the role of Chinese heritage languages, particularly among the younger generation of ethnic Chinese in Malaysia. Little is known about how this shift is affecting the middle-age and older generations who are used to communicating in Chinese heritage languages. Hence, this study examines the language practices of middle-age and older ethnic Chinese living in Penang, a state with a long-standing history of Chinese settlement. Data were collected through semi-structured interviews conducted with 43 participants. The findings show that language shift is evident among both generations as they adapt to the present trend of speaking Mandarin Chinese with family members, particularly the younger generation. However, they switch back to Chinese heritage languages during communication among their own generation. This study concludes that such language shift and accommodation is detrimental to the Chinese-Malaysian community as they face losing their heritage languages in the near future.